Nâdi Shodhan Pranâyâma: A promising intervention in improving PEFR and AQOL in adolescent girls. - U. Yadav, Deepmala; Bansal, Vidushi (International Research Journal of Ayurveda & Yoga, 2025)
This pilot study under CCRAS SPARK evaluated the effectiveness of Nadi Shodhan Pranayama on pulmonary function, specifically PEFR, and its impact on the quality of life in adolescents. The randomized controlled trial involved 60 healthy adolescents aged 12-15 years, divided equally into an intervention group practicing NSP for 15 min daily for 3 weeks and a control group following usual activities for three weeks. The PEFR measurements were recorded at baseline and post-intervention. The quality of life was assessed using the KIDSCREEN 10 questionnaire. The results showed a significant improvement in PEFR values in the NSP group compared with the control group (p < 0.0001). Additionally, the NSP group exhibited a marked enhancement in overall quality of life, suggesting that NSP is an effective, non-pharmacological intervention for enhancing pulmonary function and quality of life in adolescents. Further research is needed to explore the long-term effects and potential mechanisms underlying the benefits of NSP.